2021
DOI: 10.1021/acsanm.1c01181
|View full text |Cite
|
Sign up to set email alerts
|

SiO2-Coated Fe3O4 Nanoparticle/Polyacrylonitrile Beads for One-Step Lipase Immobilization

Abstract: Nanoscale particle-based enzyme immobilization carries a risk of dissolving or breaking the material when applied. One effective strategy to improve the stability and functionality of this type of nanomaterial is compounding with polymers. In this study, Fe3O4 nanoparticles were synthesized and coated with SiO2, after which magnetic hollow composite beads with nanoscale porous structures, named, lipase/Fe3O4/PAN (L/FP), were fabricated by compounding polyacrylonitrile and SiO2-coated Fe3O4 nanoparticles to imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 73 publications
0
9
0
Order By: Relevance
“…In our previous work, we fabricated magnetic PAN composite beads with rich nanosized pores (specific surface area of 23 m 2 ·g –1 , pore volume of 0.13 cm 3 ·g –1 , and average pore size of 22 nm), good magnetism (paramagnetism of 9.9 emu·g –1 ), good thermal and chemical stabilities, and good mechanical strength. These beads were used to physically immobilize CALB with favorable performance through one-step phase inversion . However, we observed that if the immobilized CALB was washed with 50% EtOH after the 10th cycle, then their activity increased by over 20% in the 11th cycle.…”
Section: Introductionmentioning
confidence: 89%
“…In our previous work, we fabricated magnetic PAN composite beads with rich nanosized pores (specific surface area of 23 m 2 ·g –1 , pore volume of 0.13 cm 3 ·g –1 , and average pore size of 22 nm), good magnetism (paramagnetism of 9.9 emu·g –1 ), good thermal and chemical stabilities, and good mechanical strength. These beads were used to physically immobilize CALB with favorable performance through one-step phase inversion . However, we observed that if the immobilized CALB was washed with 50% EtOH after the 10th cycle, then their activity increased by over 20% in the 11th cycle.…”
Section: Introductionmentioning
confidence: 89%
“…Silica-coated magnetic Fe 3 O 4 was prepared from the previous method. 63 The Fe 3 O 4 @SiO 2 (0.5 g) was mixed into 50 mL of toluene using ultrasonic agitation, followed by dropwise addition of APTMS (2.86 mmol) while vigorously stirred and refluxed for 24 h. After being functionalized with amine groups, the APTMS/MNP residue was extracted using an external magnet, rinsed thrice with 20 mL of toluene, and dried for 12 h at 80 C. The presence of an amino group was confirmed using the ninhydrin test. A small amount of the compound was treated with a 5% ninhydrin solution in a water bath.…”
Section: Synthesis Of Aptms/mnpmentioning
confidence: 99%
“…1 Silica (SiO 2 )-based materials have been extensively investigated for immobilization of enzymes. 2,3 The enzyme immobilizations can be categorized into three types, encapsulation using SiO 2 capsules, 4,5 core SiO 2 nanoparticles coated with functional materials for enzyme immobilization, 6−8 and enzymes embedded in nano-and microporous SiO 2 . 9,10 Using metal−organic framework ZIF-8 nanoparticles as templates, glucose oxidase and horseradish peroxidase were coencapsulated by SiO 2 capsules.…”
Section: Introductionmentioning
confidence: 99%
“…4 Fe 3 O 4 nanoparticles coated with SiO 2 were used as templates for preparing hollow porous nanocomposites to immobilize lipase. 5 Silica microspheres were coated with polyethyleneimine (PEI) and polydopamine (PDA), and PDA/PEI-SiO 2 was used to immobilize carbonic anhydrase. 6 SiO 2 nanoparticles were coated with the functional peptide and can specifically immobilize SpyTag-fused enzymes xylanase and lichenase through covalent bonding.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation